The Influence of Career Planning on Career Thoughts in STEM‐Interested Undergraduates. Issue 2 (8th June 2018) - Belser, Christopher T.; Prescod, Diandra J.; Daire, Andrew P.; Dagley, Melissa A.; Young, Cynthia Y.
Abstract : Undergraduate career planning courses have shown efficacy in decreasing students' negative career thoughts; however, universities have minimally applied these courses to science, technology, engineering, and math (STEM) populations. This study compared the influence of a STEM‐focused career planning course for undecided STEM students with a seminar course for decided STEM majors. An analysis of covariance with covariate adjustment revealed that undecided career planning students had lower adjusted mean scores on a measure of negative career thinking than the decided STEM majors after the first semester of college. The results provide support for the efficacy of STEM‐focused career planning courses and measuring negative career thoughts with STEM undergraduates.